Pelatihan Peningkatan Kapasitas Pendampingan Koperasi dan Penyusunan Proposal Akses Permodalan Bank Himbara di Desa/Kelurahan Merah Putih di Provinsi Papua Selatan - Adi Maulana Rachman; Okto Irianto; Esy D. Lewaherilla; Agustinus Fangohoy; Marthen A.I. Nahumury; Ely Noor; Fenty Y. Manuhuttu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Cooperatives at the village/sub-district level play a strategic role in driving the people's economy, yet they are frequently constrained by limited managerial capacity and access to formal capital. This community service program, organized by the Provincial Government of South Papua, aims to enhance the capacity of cooperative managers through business mentoring and the formulation of bankable credit proposals for Himbara Banks (State-Owned Banks). This activity featured Adi Maulana Rachman, a lecturer from Universitas Musamus (Unmus), as the keynote speaker and was attended by cooperative management representatives from four regencies in South Papua Province, focusing the workshop on the Merah Putih Village/Sub-district Cooperative. The implementation method was carried out through three stages: material presentation (theory), proposal drafting workshop (practice), and post-training mentoring. The results of the activity indicated a 75% increase in the partners' understanding regarding cooperative regulations and capital application techniques, alongside the compilation of draft business proposals ready to be submitted to banking institutions. This program is expected to accelerate the capitalization of cooperative businesses in the South Papua region. Keywords: Training, Cooperative, Economy, Capital, Regulation